A Review of Web Evaluation Criteria for E-Commerce Web Sites - Goi, Chai (ARRAY Development, 2012)
Few sets of criteria are available on the Web and from the researchers’ Web site evaluation criteria. Most of these Web site evaluations focus on Web site attributes, organisation and technology. The most common Web site criteria to be applied are quality, function, credibility, reliability, attractiveness, systematic structure and navigation.